Reporting Bias in Coverage of Iran Protests by Global News Agencies. (January 2022) - Adegbola, Oluseyi; Gearhart, Sherice; Cho, Janice
This study examines reporting on protests in Iran between late December 2017 and early January 2018 by global news agencies located in the United States (Associated Press [AP]), United Kingdom (Reuters), France (Agence France-Presse [AFP]), China (Xinhua), and Russia (Telegraph Agency of the Soviet Union [TASS]). A census of reporting on the protests ( N = 369) was content analyzed. Results demonstrate that news agencies varied considerably in their portrayal of issues defined as problems, diagnosis of causes, moral evaluations, and treatment recommendations. Reporting by Xinhua differed considerably from Western news agencies and featured a greater proportion of stories recommending maintenance of the status quo in Iran. Calls for political change received more attention in privately owned news agencies based in democratic nations. While the use of sources in news stories was generally similar across agencies, protesters were absent in reporting by state-owned agencies. Results conclude that differences in national interests and/or ownership of global news agencies may explain findings and provide insight into news reporting on foreign protest.